2013
DOI: 10.1002/maco.201307303
|View full text |Cite
|
Sign up to set email alerts
|

Effect of DyF3 on the corrosion behavior of hot‐pressed Nd–Fe–B permanent magnets

Abstract: The grain boundary diffusion process (GBDP) with DyF3 is a promising method to obtain excellent magnetic properties in Nd–Fe–B permanent magnets. Compared to conventionally prepared (Dy,Nd)–Fe–B magnets the overall content of the precious heavy rare earth Dy is reduced. Thus, the GBDP with DyF3 is highly attractive to cut down costs and save resources. However, it is not well known how the addition of DyF3 affects the corrosion resistance of Nd–Fe–B permanent magnets. In this work, the anodic polarization beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…The other trifluoride compound of great interest is DyF 3 . Recent research showed that DyF 3 powders could significantly improve the properties of Nd-Fe-B magnets [22][23][24][25]. In addition, DyF 3 is an important component of oxyfluoride glasses [26].…”
Section: Introductionmentioning
confidence: 99%
“…The other trifluoride compound of great interest is DyF 3 . Recent research showed that DyF 3 powders could significantly improve the properties of Nd-Fe-B magnets [22][23][24][25]. In addition, DyF 3 is an important component of oxyfluoride glasses [26].…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers have utilized rare earth fluorides (RE-F 3 ) as dopant or surface diffusion agents, to increase the coercivity in sintered magnets; with the coercivities reaching up to 2790 kA/m (35 kOe) [21,22,23,24,25,26,27,28,29,30,31,32] and in rapidly consolidated melt-spun ribbons, where coercivities reached up to 1990 kA/m [33,34]. On the contrary, no such research has been made on the HDDR Nd-Fe-B powders, which is a relatively cheap hydrogen reprocessing alternative for the EOL magnetic products [6].…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al [10] showed that the diffusion of the low-melting alloy, DyF 3 , along the parallel c-axis was better than that in the vertical direction, which was conducive to improving magnetic properties and reducing HRE consumption. Sueptitz et al [11] found that the diffusion of DyF 3 was conducive to the passivation of magnets under acidic conditions, showing better corrosion resistance. Komuro et al [12] obtained an improvement in coercivity and lowered the loss of remanence through the Dy-F diffusion coating.…”
Section: Introductionmentioning
confidence: 99%